Pengaruh Akuntabilitas Dan Transparansi Terhadap Pengelolaan Anggaran Dana Bos Di Smp Negeri Kaway XVI Kabupaten Aceh Barat - Sri Tawar S Bako; Cut Sri Firman Hastuti; Said Mahdani Mahdani (Universitas Teuku Umar, 2026)
This research aims to determine the influence of transparency and accountability in management of BOS funds at Kaway State Middle School, West Aceh Regency. This research is based on agency theory. This research use quantitative methods. The data used consists of primary data on form of questionnaire. The object of this research is budget management at Kaway State Middle School, West Aceh Regency. The research population was all Kaway State Middle School employees. The data collection technique uses a Likert scale. The data analysis method was carried out through descriptive statistics to describe the characteristics of the research variables, as well as multiple linear regression with the help of the SPSS version 26 application. Data instrument tests were validity and reliability tests. And classical assumption tests were carried out which heteroscedasticity tests, multicollinearity tests, included normality tests. Hypothesis testing is carried out through the f test, t test, coefficient of determination. The research results show that Accountability has a positive and significant effect on Budget Management, Transparency has a positive and significant effect on Budget Management, and Accountability and Transparency have a simultaneous effect on Budget Management.